Faktor yang Memengaruhi Minat dan Kesulitan Belajar Matematika Siswa Tingkat Sekolah Dasar - Sarah Safira; Ibnu Muthi (Jurnal Pendidikan, Bahasa dan Budaya, 2024)
The recurring issue in the education sector is the low interest in learning and the difficulties children face in learning at school, particularly in Mathematics. These two aspects are crucial to address and minimize as they significantly impact students' learning outcomes. This study aims to identify the factors that influence children's interest in learning and the emergence of difficulties in learning Mathematics at the elementary school level. This research employs the Systematic Literature Review (SLR) method. Data were collected through the documentation of all articles related to interest and difficulties in learning Mathematics at the elementary school level from 2019-2023. Subsequently, the researchers reviewed these articles comprehensively. The articles used in this study include both national and international journal articles. The research findings indicate that there are two factors influencing interest and difficulties in learning Mathematics: internal factors (factors within the students) and external factors (environmental factors).